Effects of probiotic, prebiotic and synbiotic intake on blood enzymes and performance of Japanese quails (Coturnix Japonica) - BABAZADEH, D; VAHDATPOUR, T; NIKPIRAN, H; JAFARGHOLIPOUR, M A; VAHDATPOUR, S (The Indian Journal of Animal Sciences, 2011)
The present study was conducted to evaluate the influence of probiotic, prebiotic and synbiotic on performance values and blood enzymes of Japanese Quails. One-day old Japanese quail chicks (192), mean body weight 7.78 g, were randomly assigned in 4 treatments and 4 replicates. The experimental diets consisted of a basal diet without additive (control), 0.2 g/kg probiotic (P), 1.6 g/kg prebiotic (F) and 1.0 g/kg synbiotic (B) added to the basal diet. Birds fed synbiotic showed that a significant elevation in body weight compared to other groups. Feed intake of birds fed synbiotic and prebiotic were higher than control and probiotic fed groups. Birds fed synbiotic exhibited a better feed conversion ratio (3.08) compared to probiotic fed (3.19) and control groups (3.14) (P<0.05). The males fed additives showed decrease in liver weight. Females fed prebiotic showed decrease in liver weight compared to control and synbiotic-additive groups. The relative weight of heart was decreased in the males fed prebiotic compared to synbiotic fed and control groups. The females fed probiotic showed increase in heart weight. The activity of ALP in males elevated by synbiotic consumption. ALP activity decreased in females fed additives. ALT activity was depressed in males fed probiotic or symbiotic. AST activity in males fed prebiotic elevated . In both gender CPK activity was higher in prebiotic feeding group. Results indicated that using synbiotics has positive effects on performance and normal activity of enzymes and prebiotic has positive effects on performance and reduction weigh of heart and liver in Japanese quails.